Assessment of Microbial Variation and Chemical Composition in Water Kefir Over Repeated Brewing Cycles and Refrigerated Storage. (7th June 2021) - Dankwa, Adwoa; Perry, Jennifer; Perkins, Lewis
Abstract: Objectives: Water kefir is a fermented beverage with potential probiotic effects. Its production requires a starter culture known as 'grains' and a sweetened water substrate. These grains self-propagate for use in sequential brewing cycles. Changes in microbial composition and its metabolites with repeated grain usage and prolonged storage are unknown. This may result in loss of functional properties or reduced consumer acceptability. This study evaluates the stability and functional components of microbial communities and chemical compositions in water kefir products over repeated brewing cycles and during refrigerated storage. Methods: Six cultures were obtained from commercial suppliers (n = 5) or homebrewers (n = 1). Each culture system was brewed following a simplified standard recipe for 20 repeated cycles. Samples were collected at pH 4 and stored at 4 oC for analysis at predetermined time points (2, 6 and 12 weeks). Samples were enumerated for total aerobic bacteria, lactic acid bacteria (LAB), acetic acid bacteria (AAB) and yeast on TSA, MRS, ABS, and APDA media respectively. HPLC was used for simultaneous detection of the major organic acids, sugars, and alcohol in water kefir. Data was subject to ANOVA, MANCOVA, and mapping for visualization. Results: Microbial population and chemical profile of water kefir were significantly affected by both repeated brewing cycles and storage. All brewing cycles at the initial 2-week storage time did not significantly affect LAB (range: 5.5–5.7 Log CFU/g) or AAB (range: 5.2–5.4 Log CFU/g) populations. However, significant variations were seen at the 12-week storage in these populations resulting in a reduction of 1.8–2.1 Log CFU/g. Overall, the microbial communities and their metabolite concentration increased until the 10th brewing cycle and then declined to their lowest at the 20th cycle. Hydrolysis of sucrose into component monosaccharides decreased from weeks 2 to 12 for brewing cycles 1 and 10; and increased at brewing cycle 20 over all storage time. Ethanol concentration was significantly lower at the 10th and 20th brewing cycles. Conclusions: This data suggests that repeated brewing beyond a certain threshold cycle adversely affects the stability and viability of the microbial culture. There is a need to limit the number of brewing cycles to achieve the optimum health benefits of water kefir. Funding Sources: USDA-NIFA.